2019
DOI: 10.3390/genes10050366
|View full text |Cite
|
Sign up to set email alerts
|

Micronuclei and Genome Chaos: Changing the System Inheritance

Abstract: Micronuclei research has regained its popularity due to the realization that genome chaos, a rapid and massive genome re-organization under stress, represents a major common mechanism for punctuated cancer evolution. The molecular link between micronuclei and chromothripsis (one subtype of genome chaos which has a selection advantage due to the limited local scales of chromosome re-organization), has recently become a hot topic, especially since the link between micronuclei and immune activation has been ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 96 publications
(220 reference statements)
1
96
0
Order By: Relevance
“…In fact, chromosomal profiles have extensively been associated with prognosis in MM, based on specific translocation, hyperdiploidy, chromosomal amplification/deletion, and chromosomal copy number abnormalities (Garcia-Sanz et al, 1995;Avet-Loiseau et al, 2007, 2009Walker et al, 2010;Shah et al, 2018). By converting DNA sequence data into aneuploidy data, we showed that the status of aneuploidy can suggest clinical MM outcomes (Ye et al, 2019a). (2) Cancer often represents an evolutionary trade-off of cellular variation-mediated function.…”
Section: Adaptive Systemsmentioning
confidence: 97%
See 1 more Smart Citation
“…In fact, chromosomal profiles have extensively been associated with prognosis in MM, based on specific translocation, hyperdiploidy, chromosomal amplification/deletion, and chromosomal copy number abnormalities (Garcia-Sanz et al, 1995;Avet-Loiseau et al, 2007, 2009Walker et al, 2010;Shah et al, 2018). By converting DNA sequence data into aneuploidy data, we showed that the status of aneuploidy can suggest clinical MM outcomes (Ye et al, 2019a). (2) Cancer often represents an evolutionary trade-off of cellular variation-mediated function.…”
Section: Adaptive Systemsmentioning
confidence: 97%
“…However, they have often been ignored due to the popularity of gene-centric concepts. Changing the karyotype coding is a hallmark of somatic and organismal macroevolution (Heng, 2019;Ye et al, 2019a).…”
Section: Karyotype Coding Vs Gene Codingmentioning
confidence: 99%
“…Single cell approaches have also been developed to quantify and compare surrogate markers of CIN (e.g., CIN-associated phenotypes), including micronucleus formation [28,29] and changes in nuclear areas [29] or human artificial chromosomes [30]. Conceptually, micronuclei are extra nuclear bodies that are found outside the primary nucleus and are hallmarks of CIN that typically arise due to chromosome missegregation events [31][32][33], while changes in nuclear areas and human artificial chromosomes are associated with small and large (i.e., ploidy) scale changes in DNA content, respectively [30,[34][35][36][37][38]. These approaches typically involve quantitative imaging microscopy or flow cytometry that are each capable of rapidly assessing CIN-associated phenotypes in hundreds-to-thousands of cells [28,29,39].…”
Section: Fundamental Concepts In Assessing Cin: Benefits and Limitationsmentioning
confidence: 99%
“…One final consideration stems from the lack of evidence for RNA-protein 5′ phosphotyrosyl bonds similar to those linking VPg to the viral RNA in uninfected human cells and how the presence of DNA linked to protein by 5′ phosphotyrosyl bonds in the cytoplasm might be a putative signal for the activation of innate immune pathways [65]. It is conceivable that picornaviruses have evolved to ensure that this type of linkage is not recognized by the host via hydrolysis of VPg from the RNA immediately upon infection and during the early stages of replication.…”
Section: Figure 14mentioning
confidence: 99%